Respostas
respondido por:
7
2x+y= 1
2x = 1-y
x = (1-y)/2
4(1-y)/2 + 3y = 7
(4-4y)/2 + 3y = 7
2-2y+3y = 7
2+y = 7
y = 5
2x+5 = 1
2x = -4
x = -2
x = -2 ; y = 5
2x = 1-y
x = (1-y)/2
4(1-y)/2 + 3y = 7
(4-4y)/2 + 3y = 7
2-2y+3y = 7
2+y = 7
y = 5
2x+5 = 1
2x = -4
x = -2
x = -2 ; y = 5
respondido por:
3
2x+y=1
4x+3y=7
Resolução:
2x+y=1
y=1-2x
Substitui o valor de y na outra equação:
4x+(1-2x)=7
4x+1-2x=7
4x-2x=7-1
2x=6
x=6/2
x=3
Agora vamos encontrar o valor de y:
y=1-2x
y=1-2*3
y=1-6
y=-5
4x+3y=7
Resolução:
2x+y=1
y=1-2x
Substitui o valor de y na outra equação:
4x+(1-2x)=7
4x+1-2x=7
4x-2x=7-1
2x=6
x=6/2
x=3
Agora vamos encontrar o valor de y:
y=1-2x
y=1-2*3
y=1-6
y=-5
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás